Reconstructing past seawater pH from boron isotopes in carbonates - Pelejero, Carles; Calvo, Eva María (Institut d'Estudis Catalans, 2007)
Special issue Paleoclimatology research in Catalonia.-- 10 pages, 6 figures [EN] Since the Industrial Revolution, the CO2 concentration in the atmosphere has increased substantially, enhancing the greenhouse effect, which is very much related to current global warming. Fortunately, the Earth has a series of reservoirs, especially its oceans, which trap a significant amount of the excess CO2. This marine absorption of CO2, however, results in progressive acidification of the oceans, which has detrimental and possibly devastating effects for marine organisms, particularly those that construct a skeleton of calcium carbonate (corals, mussels, clams, etc.). To understand the magnitude of this problem, it is crucial to know how seawater pH has oscillated in the past, particularly during those periods of time that are not covered by instrumental measurements, which are restricted to the last decade. For this purpose, the isotopic composition of boron in fossil biogenic carbonates provides a geochemical indicator, or proxy, which allows reconstruction of the past variations in seawater pH. In this review, we explain the theoretical grounds of this proxy, show the empirical calibrations carried out so far, briefly comment on some aspects of boron isotope analysis, and list the results of paleo-pH reconstructions published so far [CAT] Des de la revolució industrial, la concentració de CO2 a l'atmosfera ha augmentat de manera molt significativa, amb el consegüent augment de l'efecte d'hivernacle, molt relacionat amb l'actual escalfament global. Per sort, la Terra disposa d'una sèrie de reservoris, sobretot els oceans, que atrapen una quantitat significativa d'aquest excés de CO2. No obstant això, com a resultat de l'absorció marina de CO2, les aigües s'estan acidificant progressivament i comprometran, potser de manera devastadora, el desenvolupament d'organismes marins, sobretot d'aquells que construeixen un esquelet de carbonat (coralls, musclos, cloïsses, etc.). Per entendre l abast d'aquest problema, és molt ...